2019
DOI: 10.3390/toxins11010058
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Marine Toxins and the Associated Seafood Poisoning Episodes in the African Countries of the Indian Ocean and the Red Sea

Abstract: The occurrence of Harmful Algal Blooms (HABs) and bacteria can be one of the great threats to public health due to their ability to produce marine toxins (MTs). The most reported MTs include paralytic shellfish toxins (PSTs), amnesic shellfish toxins (ASTs), diarrheic shellfish toxins (DSTs), cyclic imines (CIs), ciguatoxins (CTXs), azaspiracids (AZTs), palytoxin (PlTXs), tetrodotoxins (TTXs) and their analogs, some of them leading to fatal outcomes. MTs have been reported in several marine organisms causing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 297 publications
(280 reference statements)
0
16
0
Order By: Relevance
“…Investigations have found that the distribution of MCs in freshwater habitats is a matter of concern, and MCs are typically produced by several cyanobacterial genera including Anabaena , Dolichospermum , Geitlerinema, Leptolyngbya , Microcystis , Nostoc , Phormidium and Planktothrix [13]. In addition, MCs have also been found in many marine cyanobacteria [14] such as Spirulina, Synechococcus and Trichodesmium (Table 1).…”
Section: Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations have found that the distribution of MCs in freshwater habitats is a matter of concern, and MCs are typically produced by several cyanobacterial genera including Anabaena , Dolichospermum , Geitlerinema, Leptolyngbya , Microcystis , Nostoc , Phormidium and Planktothrix [13]. In addition, MCs have also been found in many marine cyanobacteria [14] such as Spirulina, Synechococcus and Trichodesmium (Table 1).…”
Section: Structural Characterizationmentioning
confidence: 99%
“…More than twelve cyanobacterial toxins have been found in the oceans across the world. MCs have been found in the marine environments of the central Atlantic coast of Portugal, the Canary Islands, the Brazilian coast, the Amvrakikos Gulf, and the Indian Ocean [14]. BMAA was reported from Guam in the western Pacific, and Bermuda in the western region of North Atlantic [52].…”
Section: Distribution Of Cyanotoxinsmentioning
confidence: 99%
“…Cyanotoxins and phycotoxins are secondary metabolites produced by harmful algal blooms of toxic phytoplankton species or photosynthetic microorganisms such as cyanobacteria (green–blue algae), which are found in both freshwater habitats and marine environments [1]. The toxins are bioaccumulated by marine organisms, meaning that they may enter the human food chain.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the contaminants are non-biodegradable, putting at risk living organisms and human health due to bioaccumulation [3,4]. Within this context, European Union monitoring programs have currently included three groups of toxins: Diarrheic shellfish toxins (DSTs), paralytic shellfish toxins (PSTs), and amnesic shellfish toxins (ASTs), and some other lipophilic contaminants [5].…”
Section: Introductionmentioning
confidence: 99%